Residual disease is a strong prognostic marker in patients with acute lymphoblastic leukaemia with chemotherapy‐refractory or relapsed disease prior to allogeneic stem cell transplantation. (22nd June 2021) - Nakamura, Momoko; Arai, Yasuyuki; Hirabayashi, Shigeki; Kondo, Tadakazu; Doki, Noriko; Uchida, Naoyuki; Fukuda, Takahiro; Ozawa, Yukiyasu; Tanaka, Masatsugu; Sawa, Masashi; Katayama, Yuta; Kanda, Yoshinobu; et al.
Summary: Allogeneic haematopoietic stem cell transplantation (allo‐HSCT) is one of the curative treatment options for acute lymphoblastic leukaemia (ALL). However, the outcomes in patients transplanted without complete remission (non‐CR) have not yet been fully reported, and detailed analyses are required to identify subgroups in which optimal prognosis is expected and to optimize pre‐transplant therapeutic strategies. Hence, we performed a multicentred retrospective cohort study including a total of 663 adult ALL patients transplanted at non‐CR status; the median bone marrow (BM) blast counts at HSCT was 13·2%, and 203 patients (30·6%) were treated at primary induction failure status. The overall survival (OS) was 31·1% at two years, and the multivariate analyses identified five prognostic risk factors, including older age (≥50 years), increased BM blasts (≥10%), poor performance status, high haematopoietic cell transplantation (HCT)‐comorbidity index, and relapsed disease status, among which BM blast was the most significantly related. A predictive scoring system composed of these risk factors clearly stratified OS (15·6–59·5% at two years). In conclusion, this is the first large‐scale study to analyze the correlation of patient characteristics with post‐transplant prognosis in ALL transplanted at non‐CR status. The importance of blast control before HSCT should be focused on for better patient prognosis.